Consistency in organization (updated) - Ekkehart Schlicht (Institute for the Study of Labor (IZA), 2011)
Internal organization relies heavily on psychological consistency requirements. This thought has been emphasized in modern compensation theory, but has not been extended to organization theory. The perspective sheds new light on several topics in the theory of the firm, like the boundaries of the firm, the importance of fairness concerns within firms, the attenuation of incentives, or the role of routines and incentives. It implies a perceptional theory of the firm that is realistic in the sense advocated by Ronald Coase (1937).
urn:nbn:de:101:1-201104193318
Keywords: B52; D02; L2; 330; theory of the firm; hierarchy; evolutionary theory of the firm; perceptional theory of the firm; consistency; small numbers; centralization paradox; Williamson's puzzle; compensation; boundaries of the firm; fairness; idiosyncratic exchange; entitlements; obligations; routines; framing; Simon; employment relationship; fairness; ownership effect; skunkworks; disruptive technologies; Tayloristic organization; holistic organization; Arbeitsorganisation; Theorie der Unternehmung; Leistungsanreiz; Organisationstheorie; Theorie